Effects of neurofibromatosis type 1 on children's development - Haynes, Norris M.; Kirwan, Jacqueline R.; McCrohan, Kelly (Social Work in Public Health, 2011)
In-depth study of the human genome holds the potential to provide needed focus on genetic disorders that affect hundreds of thousands of children and significantly affect their development. Neurofibromatosis Type-1 (NF-1) is one of the most common genetic disorders that affect neurological, cognitive, social, and physical development. NF-1 affects all racial groups and both genders equally. NF-1 occurs in about 1 in 2,500 to 3,300 individuals in the population. The incidence rate at birth is about 0.0004 births in the United States and is growing in prevalence. Children with NF-1 experience a range of psychomotor and cognitive impairments that affect the quality of their social lives and their learning and academic achievements. Interventions to address the psychosocial and educational needs of children with NF-1 include a range of social and academic support services, which are most effective when they are comprehensive, involve a multidisciplinary team of educational and health experts, and include a focus on supporting and empowering family members to be effective caregivers. Efforts to address the needs of children with NF-1 and to provide adequate support to their families have significant policy implications for local, state, and federal officials.
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00264 tex.type: [object Object]
Keywords: *Child Development; *Genome; Human; *Neurofibromatosis 1/px [Psychology]; *School Health Services; Adolescent; Adult; Aged; Child; Child Development; Child Welfare; Child; Preschool; Emotions; Female; Genome; Human; Humans; Infant; Infant; Newborn; Male; Middle Aged; Neurofibromatosis; Neurofibromatosis 1; Neurofibromatosis 1/di [Diagnosis]; Neurofibromatosis 1/ep [Epidemiology]; Neurofibromatosis 1/ge [Genetics]; Patient Education as Topic; Power (Psychology); Power; Psychological; Prevalence; Risk Factors; School Health Services; Social Change; Social Work; United States; United States/ep [Epidemiology]; Young Adult; adolescent; adult; aged; article; behavior; birth rate; child; child development; child health; child welfare; cognition; dept.psy; disease incidence; disease prevalence; emotion; family empowerment; female; genetics; genome; heritability; human; human genome; infant; male; mental health; middle aged; neurofibromatosis; newborn; patient education; peer-reviewed; preschool child; prevalence; psychological aspect; psychology; risk factor; school health service; school psychologists; school-based interventions; social and emotional development; social change; social policy; social work